The challenge of addressing obesity in people with poorly controlled asthma - Anne E. Dixon; Kathryn V. Blake; Emily A. DiMango; Mark T. Dransfield; Laura C. Feemster; Olivia Johnson; Gem Roy; Heather Hazucha; Jean Harvey; Meredith C. McCormack; Robert A. Wise; Janet T. Holbrook (Wiley, 2021)
Abstract Objective There is a high prevalence of obesity in people with asthma, and obesity is associated with poorly controlled asthma. Significant weight loss might improve asthma control: the purpose of this study was to investigate patient characteristics and factors that might affect implementation of a weight loss and/or roflumilast intervention, to target both obesity and asthma. Methods A cross‐sectional study of people with obesity and poorly controlled asthma performed at 13 sites across the United States. Results One hundred and two people participated in this study. Median BMI was 37 (IQR 35-42). The majority, 55%, were African American and 76% were female. Fifty two percent had very poorly controlled asthma. Most participants were quite sedentary (70% reported being inactive or participating only in light‐intensity activities according to the Stanford Brief Activity Survey). Participants reported significant impairments related to physical function on the Impact of Weight on Quality of Life‐Lite questionnaire (median score 67 [IQR 41-84]). Thirty‐five percent of participants reported mild, and 2 % moderate, depressive symptoms as assessed by the Patient Health Questionnaire‐9. Conclusions Poorly controlled asthma and obesity often affect minority populations and are associated with significant impairments in health related to physical function and low levels of physical activity that might complicate efforts to lose weight. Interventions targeted at poorly controlled asthma associated with obesity in the United States need to address factors complicating health in underserved communities, such as increasing opportunities for physical activity, while also managing activity limitations related to the combination of asthma and obesity.